Ectopic pregnancy in a tertiary care centre of Jharkhand, India - Parashar, Meetali; Mehta, Meena (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Ectopic pregnancy is one in which the fertilized ovum is implanted and develops outside the endometrial cavity. It is an important cause of maternal morbidity and mortality in first trimester. The present study was conducted to study the risk factors, clinical presentation and management of ectopic pregnancy in RIMS, Ranchi, Jharkhand, India. Methods: This was a prospective study conducted in the department of obstetrics and gynaecology, RIMS, Ranchi, Jharkhand during May 2017 to September 2018. A total of 90 cases were included in the study. Results: 80% of the patients presented with amenorrhoea, 98% had abdominal pain and 69% had vaginal bleeding. Ultrasonography revealed hemoperitoneum in about 93% patients. 16 (18%) patients had history of infertility whereas 10 patients (11%) had taken treatment of infertility.6 (7%) patients had history of STD or PID.14 (16%) had undergone bilateral tubectomy.2 (2%) had history of IUCD insertion and 12 (13%) patients had undergone previously lscs. 54 patients (60%) had undergone D and C and 6 patients (7%) had a previous history of ectopic pregnancy. 68 (76%) underwent only salpingectomy.12 (13%) had salpingo-oophorectomy and 10 (11%) had salpingectomy with contralateral tubectomy. Conclusions:Diagnosis of ectopic pregnancy requires clinical suspicion and supportive investigations like UPT, ultrasonography, β HCG and laparoscopy. It is an important cause of admission to RIMS as maternal near miss cases. Background: Ectopic pregnancy is one in which the fertilized ovum is implanted and develops outside the endometrial cavity. It is an important cause of maternal morbidity and mortality in first trimester. The present study was conducted to study the risk factors, clinical presentation and management of ectopic pregnancy in RIMS, Ranchi, Jharkhand, India. Methods: This was a prospective study conducted in the department of obstetrics and gynaecology, RIMS, Ranchi, Jharkhand during May 2017 to September 2018. A total of 90 cases were included in the study. Results: 80% of the patients presented with amenorrhoea, 98% had abdominal pain and 69% had vaginal bleeding. Ultrasonography revealed hemoperitoneum in about 93% patients. 16 (18%) patients had history of infertility whereas 10 patients (11%) had taken treatment of infertility.6 (7%) patients had history of STD or PID.14 (16%) had undergone bilateral tubectomy.2 (2%) had history of IUCD insertion and 12 (13%) patients had undergone previously lscs. 54 patients (60%) had undergone D and C and 6 patients (7%) had a previous history of ectopic pregnancy. 68 (76%) underwent only salpingectomy.12 (13%) had salpingo-oophorectomy and 10 (11%) had salpingectomy with contralateral tubectomy. Conclusions: Diagnosis of ectopic pregnancy requires clinical suspicion and supportive investigations like UPT, ultrasonography, β HCG and laparoscopy. It is an important cause of admission to RIMS as maternal near miss cases.